Serum Zinc and Copper Changes in Male Infertility - ibrahim, Hadee (Iraqi National Journal of Nursing Specialties, 2013)
Objective: The aim of this study to detect the correlation between trace elements such as zinc, copper and spermatogenesis, sperm viability and motility. Methodology: Serum and semen samples were collected from one hundred twenty patients with age ranged (20- 50 years) attending the high institute for Embryo Research and Infertility Treatment/ Baghdad University, in addition to thirty fertile males their age comparable to that of patients. The period of this study was from June 2004 until the end of October 2004. Results: The result of routine seminal fluid analysis of all infertile males was divided according to WHO, (1999) limit into four groups: Asthenospermia(A), Asthenoteratospermia(AT), Oligoasthenoteratospermia OAT and Azoospermia(Azoo), each group includes thirty patient. Results showed highly significant decrease in serum zinc concentration in different infertile groups compared to control group, and a slight increase in serum copper concentration in different infertile group. With advancing age, all the infertile groups, as well as the control group, had a slight decrease in serum concentration of zinc, and a slight increase in serum copper concentration. Recommendations: Further studies are needed to evaluate the levels of different biochemical parameters in seminal plasma of different infertile groups.